Ragam Fawatihu al-Suwar wa Khawatimuha dan Relasinya - Mohammad Dai Robbi; Muhamad, Fahmi (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
The Qur'an is the greatest mu'jizat owned by the Prophet Muhammad In addition, the Qur'an is one of the main sources of Islamic teachings in addition to the hadith. The study of the Qur'an has been carried out by many scholars since ancient times. They studied the Qur'an in accordance with the disciplines they mastered. The Qur'an which is a sea of knowledge will never run out of studies from various sides. One of the studies and at the same time proving the miracle of the Qur'an is the study of the opening words and closing words of each letter in the Qur'an. As it is known that the Qur'an which consists of 114 letters, apparently begins with various kinds of opening (fawatih al-suwar) and ends with various kinds of closing (khawatim al-suwar).